2012
DOI: 10.1007/s00276-012-0979-y
|View full text |Cite
|
Sign up to set email alerts
|

The human locus coeruleus 3-D stereotactic anatomy

Abstract: The human LC is a nucleus thinner and longer than previously described (in average 14.5 mm long and 2-2.5 mm thick), localized 1 mm under the IV ventricle, 3 mm apart from the midline and centered 14-21 mm above de ponto-medullary junction. No correlation was found between LC and pons dimensions, the gender or the age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
92
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(130 citation statements)
references
References 21 publications
21
92
2
2
Order By: Relevance
“…In particular, we pooled over aligned scans to facilitate LC delineation at a group level 58 , which in turn was used to restrict automatized extraction of individual peak intensities 64,65 . The LC volume of interest (search space) generated at the group level matches recent histological analyses that reported a dense packing of noradrenergic cells in a thin central LC compartment and dispersion towards rostral and especially caudal extremities 14 . We demonstrated high validity of the proposed semiautomatic procedure by comparisons to both previously published LC maps 41,58 and manual LC intensity ratings (see Supplemental results).…”
Section: Supplemental Results) These Results Bridge a Gap Between Anmentioning
confidence: 55%
See 3 more Smart Citations
“…In particular, we pooled over aligned scans to facilitate LC delineation at a group level 58 , which in turn was used to restrict automatized extraction of individual peak intensities 64,65 . The LC volume of interest (search space) generated at the group level matches recent histological analyses that reported a dense packing of noradrenergic cells in a thin central LC compartment and dispersion towards rostral and especially caudal extremities 14 . We demonstrated high validity of the proposed semiautomatic procedure by comparisons to both previously published LC maps 41,58 and manual LC intensity ratings (see Supplemental results).…”
Section: Supplemental Results) These Results Bridge a Gap Between Anmentioning
confidence: 55%
“…Its location adjacent to the ventricular system and its widespread, unmyelinated projections expose LC cells to blood-and cerebrospinal-fluid bound toxins, making them a likely target for neurodegeneration 34 . Consistent with its age-related vulnerability, a prominent, rostrally accentuated decline of LC density was reported in healthy aging (see Manaye and colleagues 18 for a review of early studies; but see 12,14,35,36 and Mather and Harley 34 for a recent discussion). Based on longitudinal data, Wilson and colleagues 10 reported initial evidence pointing to the importance of LC integrity, here assessed via LC's neuronal density, for maintaining memory abilities in old age.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Nieuwenhuys [] suggested that the cell groups A4 and A6 form the LC complex, whereas other authors suggested the cell groups A4–A7 [Pearson et al, ]. The LC proper was described as a bilateral, “tube‐like,” pigmented nucleus [Fernandes et al, ; German et al, ]. It begins rostrally in the caudolateral part of the mesencephalic central gray, at the level of the inferior colliculus (A6), and extends caudally to a position in the lateral wall of the fourth ventricle (A4) [German, et al, ].…”
Section: Discussionmentioning
confidence: 99%